Correlation between Plasma Interleukin-3, the α/β Globin Ratio, and Globin mRNA Stability. (18th November 2014) - Rouhi Dehnabeh, S.; Mahdian, R.; Ajdary, S.; Mostafavi, E.; Khatami, S.
Abstract : Background . Globin chain synthesis (GCS) analysis is used in the diagnosis of thalassemia. However, the wide reference range limits its use as a decisive diagnostic tool. It has been shown that α and β    globin mRNA increase through stimulation of cells by interleukin-3 (IL-3). Therefore, this study investigates the relationship between plasma IL-3 and the β / α    globin ratio. Methods . Blood samples were collected from 32 healthy participants on two occasions one month apart. GCS analysis, real-time PCR, and ELISA tests were conducted to determine the β / α    globin ratio, globin mRNA expression and stability rate, and IL-3 levels. Results . On the basis of IL-3 levels, the participants were divided in two groups. One group included participants who showed a significant increase in IL-3 as indicated by a significant rise in mean values of α, β, and γ    globin mRNA, α and β    globin, RBC, and hemoglobin. The other group included participants who showed no difference in IL-3 levels with no significant variations in the above-mentioned parameters. Conclusion . The results of this study indicate that IL-3 has an equivalent positive effect on α and β    globin chain synthesis. Therefore, IL-3 levels do not explain the wide reference range of the α / β    globin ratio.